2010
DOI: 10.2139/ssrn.1586778
|View full text |Cite
|
Sign up to set email alerts
|

Staying Home or Moving Away? The Effect of Restructuring on Employment in Multinational Headquarters and Their Affiliates

Abstract: This paper analyzes employment growth in Belgian multinational enterprises' headquarters relative to their affiliates. We find that headquarters have on average 2.5% more employment growth than their affiliates. When they go through restructuring headquarters reduce employment by 4.4% less than their affiliates and affiliates located further away from their headquarters suffer more. This effect almost doubles for firms that operate in manufacturing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The academic literature exploring this issue is still very scarce. Recently, Abraham et al (2010) found that Belgian MNEs' headquarters employ on average more people than their affiliates. Furthermore, employment growth in Belgian MNEs' headquarters is on average 2.5% higher than in their affiliates.…”
Section: Strategic Role Productivity and Employmentmentioning
confidence: 99%
“…The academic literature exploring this issue is still very scarce. Recently, Abraham et al (2010) found that Belgian MNEs' headquarters employ on average more people than their affiliates. Furthermore, employment growth in Belgian MNEs' headquarters is on average 2.5% higher than in their affiliates.…”
Section: Strategic Role Productivity and Employmentmentioning
confidence: 99%
“…This negative effect may be amplified by a home bias. Under adverse economic conditions, multinationals tend to safeguard employment in home‐country headquarters compared to more distant plants located abroad (see Abraham et al., ; for evidence for Belgium, Landier et al., ; Cappariello et al., ). This implies that foreign‐owned firms, which are less deeply rooted into the local economy, are less reluctant to close down their activities than domestic MNFs.…”
Section: Introductionmentioning
confidence: 99%